The Relationship of Community-Based Total Sanitation with Stunting Incidences in Toddlers - Auliya Fajriyati; Novita Rany; Jasrida Yunita; Oktavia Dewi; Emy Leonita (Journal of Health Promotion and Behavior, 2021)
Background: Stunting is a condition where toddlers have a length or height that is less than their age. The prevalence of stunting in Riau Province in 2019 based on survey data on the nutritional status of Indonesian toddlers was 23.7%, at the Sidomulyo Health Center there were 161 stunting toddlers and the results of the study found stunting toddlers 36.9%. The purpose of this study was to determine the relationship between Community Based Total Sanitation (cbts) and the incidence of stunting in children under five in the working area of the Sidomulyo Health Center Pekanbaru City in 2021.Subjects and Method: The cross-sectional study was conducted in the working area of the Sidomulyo Public Health Center, Pekanbaru, Riau, Sumatra from July to August 2021. A total of 163 subjects were selected in this study using a purposive sampling technique. The dependent variable is the incidence of stunting. The independent variables are open defecation (stop defecation), hand washing with soap, household drinking water and food management, household waste protection, and household liquid waste protection. Data were collected using a questionnaire and analyzed using chi-square test and multiple regression test.Results: Open defecation (OR= 20.25; 95% CI= 6.59 to 62.15; p<0.001), household waste management (OR= 13.84; 95% CI= 6.27 to 30.55; p<0.001), household waste (OR= 11.91; 95% CI= 5.53 to 25.58; p<0.001) associated with stunting and was statistically significant.Conclusion: Open defecation, household waste, household waste are associated with stunting and are statistically significant.Keywords: toddler, Community Based Total Sanitation, stuntingCorrespondence:Auliya Fajriyati. School of Health Sciences Hang Tuah, Pekanbaru, Indonesia. Jl. Mustafa Sari No.5, Tengkerang Selatan, Bukit Raya, Pekanbaru, Riau. Email: auliyafrh@gmail.com. Mobile: +6281261668168.Journal of Health Promotion and Behavior (2021), 06(03): 224-232DOI: https://doi.org/10.26911/thejhpb.2021.06.03.06